Increase The Share of Digital Economy in GDP and Develop This Sector (The Peerian Journal, 2023)
Humanity has been swept by a wave of serious global changes. This stage is distinguished by the breakthrough development of digital technologies, the revolution in the information space, and the acceleration of the globalization of the economy. Information has acquired the status of a key resource in social and economic processes. The penetration of digital technologies into life is one of the characteristic features of the future world. This is due to progress in the fields of microelectronics and telecommunications, IT technologies. The transition to digitalization is today one of the key priorities for the development of our state